The colours of the empire : racialized representations during Portuguese colonialism - Matos, Patrícia Ferraz de (European anthropology in translation, 2013)
The Portuguese Colonial Empire established its base in Africa in the fifteenth century and would not be dissolved until 1975. This book investigates how the different populations under Portuguese rule were represented within the context of the Colonial Empire by examining the relationship between these representations and the meanings attached to the notion of 'race'. Colour, for example, an apparently objective criterion of classification, became a synonym or near-synonym for 'race', a more abstract notion for which attempts were made to establish scientific credibility. Through her analys.